Impact of new-onset left bundle branch block on clinical and echocardiographic outcomes after TAVR with SAPIEN-3 valve. (14th October 2021) - Lak, H; Sammour, Y; Chahine, J; Chawla, S; Kadri, A; Popovic, Z; Tarakji, K; Svensson, L G; Reed, G; Puri, R; Krishnaswamy, A; Kapadia, S
Abstract: Background: New left bundle branch block (LBBB) is a common finding after transcatheter aortic valve replacement (TAVR) that can result in worse outcomes after TAVR. We aim to investigate the impact of new-onset LBBB after TAVR using the SAPIEN-3 (S3) valve. Methods: Consecutive patients who underwent transfemoral-TAVR with S3 valve between April 2015 and December 2018 were included. Exclusion criteria included pre-existing LBBB, right bundle branch block, left anterior hemiblock, left posterior hemiblock, wide QRS ≥120 msec, prior permanent pacemaker (PPM), and non-transfemoral access. Results: Among 612 patients, 11.4% developed new-onset LBBB upon discharge. Implantation depth was the only predictor of new-onset LBBB (OR 1.294; 95% CI 1.121–1.493; p<0.001). The median (IQR) length of stay was longer with new-onset LBBB [3 (2–5) days vs. 2 (1–3) days; p<0.001]. New-onset LBBB was associated with higher thirty-day PPM requirement (18.6% vs. 5.4%; p<0.001) including those implanted after discharge (4.3% vs. 0.9%; p=0.02). There was no difference in 3-year all-cause mortality between both groups (30.9% vs. 30.6%; log-rank p=0.829). Further, new-onset LBBB was associated with lower left ventricular ejection fraction (LVEF) at both 30 days (55.9±11.4% vs. 59.3±9%; p=0.026) and 1 year (55±12% vs. 60.1±8.9%; p=0.002) despite no differences at baseline. These changes were still present when we stratified patients according to baseline LVEF (≥50% or <50%). We also noted higher mean LV end-diastolic volume index (51.4±18.6 vs. 46.4±15.1 ml/m 2 ; p=0.036), and LV end-systolic volume index (23.2±14.1 vs. 18.9±9.7 ml/m 2 ; p=0.009) with new-onset LBBB at 1 year. Lastly, there were significantly higher rates of heart failure readmissions at 1 year with new-onset LBBB (10.7% vs. 4.4%; log-rank p=0.033). Conclusion: Among our cohort of S3 recipients, new-onset LBBB was associated with higher PPM requirement, worse LVEF, higher LV volumes and increased risk of heart failure hospitalizations. However, it did not affect mortality in the short-to-intermediate post-TAVR period. FUNDunding Acknowledgement: Type of funding sources: None.